Protective effects of isoflavones on alcoholic liver diseases: Computational approaches to investigate the inhibition of ALDH2 with isoflavone analogues - Lee, Wook; Kim, Seung-Jin (Frontiers in Molecular Biosciences, 2023)
Excessive and chronic alcohol intake can lead to the progression of alcoholic liver disease (ALD), which is a major cause of morbidity and mortality worldwide. ALD encompasses a pathophysiological spectrum such as simple steatosis, alcoholic steatohepatitis (ASH), fibrosis, alcoholic cirrhosis, and hepatocellular carcinoma (HCC). Aldehyde dehydrogenase (ALDH2) is the most vital enzyme that produces acetaldehyde from alcohol and is expressed at high levels in the liver, kidneys, muscles, and heart. The ALDH2*2 allele is found in up to 40% of East Asian populations, and has a significant impact on alcohol metabolism. Interestingly, several studies have shown that individuals with ALDH2 deficiency are more susceptible to liver inflammation after drinking alcohol. Furthermore, there is growing evidence of an association between ALDH2 deficiency and the development of cancers in the liver, stomach, colon, and lung. Isoflavone analogues are low molecular-weight compounds derived from plants, similar in structure and activity to estrogen in mammals, known as phytoestrogens. Recent studies have reported that isoflavone analogues have beneficial effects on the progression of ALD. This mini-review summarizes the current knowledge about the roles of isoflavone analogues in ALD and discusses the therapeutic potential of isoflavone analogues in liver pathophysiology. In particular, we highlight the significance of computational approaches in this field.